Synthesis and antimicrobial evaluation of new 1,3,4 – Thiadiazole Derivatives - Mustafa, Iman F.; Hussain, Eman M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The amino thiadiazole [I] on treatment with aromatic aldehydes yielded Schiff bases [IIa-c] , which cyclized to thiazolidinone [IIIa-c] derivatives by reaction with thioglycolic acid .Reaction of carbon disulfide and methyl iodide with [I] gavedithiomethyl[IV] which on treatment with o-phenylenediamine gave the condensed N-Imidazolythiadiazolylamine [V] , However , reaction of [I] with phenylisocyanate and phenylisothiocyanate afforded the carbamideand carbothiamide derivatives[VI.VII]a-c. The structure of these compounds was characterized from their melting point , FTIR spectroscopy and elementalanalysis